2020
DOI: 10.1111/wej.12576
|View full text |Cite
|
Sign up to set email alerts
|

Removal of hexavalent chromium from wastewater using supported liquid membrane: synthesis of chromium‐iron complex through electrochemical reaction

Abstract: Treatment of wastewater containing hexavalent chromium is the issue in this research. Supported liquid membrane with in situ electrochemical reaction in stripping section helps to reduce hexavalent chromium to trivalent chromium by forming chromium-iron complex. Iron plate acts as anode in stripping section. The chromium-iron complex is an useful value added product that can be used for various purposes such as catalyst in water-gas shift reaction. Aliquat 336 has been used as carrier for transport of hexavale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Related research works have also been carried out where more than one heavy metal was removed through precipitation [27], electrochemical reactions [28], and electrodeposition [19,29]. Based on the literature review, it has been found that the transport efficiency of As(III) is low in comparison to As(V) by the flat-sheet (FS)-SLM technique.…”
Section: Introductionmentioning
confidence: 99%
“…Related research works have also been carried out where more than one heavy metal was removed through precipitation [27], electrochemical reactions [28], and electrodeposition [19,29]. Based on the literature review, it has been found that the transport efficiency of As(III) is low in comparison to As(V) by the flat-sheet (FS)-SLM technique.…”
Section: Introductionmentioning
confidence: 99%
“…Water scarcity has been intensified by the fast growth in the industrialization of rural areas, leading to them being exposed to hazardous industrial effluents. In industry, the discharge of huge amounts of coloured wastewater containing synthetic dyes has become a global concern, as a large number of dyes are toxic and nondegradable in nature and cause serious damage to human health and aquatic ecosystems because of their complicated and stable chemical structures (Hua et al ., 2012; Ahmad et al ., 2015; Chen et al ., 2015; Lin et al ., 2015; Bouazizi et al ., 2017; Esfahani et al ., 2019; Mao et al ., 2020; Mondal and Saha, 2020). In this context, to decrease the risk of environmental pollution, dyes need to be removed from wastewater before it is discharged into the environment.…”
Section: Introductionmentioning
confidence: 99%